2018
DOI: 10.1111/tops.12337
|View full text |Cite
|
Sign up to set email alerts
|

Miscommunication in Doctor–Patient Communication

Abstract: The effectiveness of medical treatment depends on the quality of the patient–clinician relationship. It has been proposed that this depends on the extent to which the patient and clinician build a shared understanding of illness and treatment. Here, we use the tools of conversation analysis (CA) to explore this idea in the context of psychiatric consultations. The CA “repair” framework provides an analysis of the processes people use to deal with problems in speaking, hearing, and understanding. These problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 60 publications
3
84
0
3
Order By: Relevance
“…Others felt they coped well, and were satisfied with a life with lower dosages or without AP medication. These findings show how increased psychosocial intervention options support personal recovery processes like increased self-agency and motivation, which is in line with findings from other studies (54,55). However, it is important to take into consideration the possibility of risk regarding both the discontinuation process, and potential selfstigma in the use of coping strategies.…”
Section: Discussionsupporting
confidence: 89%
“…Others felt they coped well, and were satisfied with a life with lower dosages or without AP medication. These findings show how increased psychosocial intervention options support personal recovery processes like increased self-agency and motivation, which is in line with findings from other studies (54,55). However, it is important to take into consideration the possibility of risk regarding both the discontinuation process, and potential selfstigma in the use of coping strategies.…”
Section: Discussionsupporting
confidence: 89%
“…There are several points of contact between the CA analysis of repair and cognitive science. The fact that repair sequences are both incremental and jointly managed highlights the fundamentally interactive nature of these processes (see Byun, De Vos, Bradford, U., & Levinson, ; McCabe & Healey, ; Purver et al., ). This creates particular difficulties for sentential approaches to the formal semantics of dialog and alternative approaches, inspired by a consideration of patterns of misunderstanding, are also explored in Ginzburg and Kolliakou () and Larsson ().…”
Section: The Cognitive Science Of Miscommunicationmentioning
confidence: 99%
“…In adult interactions, Brennan and Schober () showed that self‐repairs in which people revise what they are saying mid‐turn, often termed “disfluencies” in linguistics, can demonstrably add to the intelligibility of speaker's turns for their addressees. McCabe and Healey () provide further evidence for the beneficial effect of the use of self‐repairs by mental health professionals on the quality of clinical interactions. In addition, there is experimental evidence that selectively interfering with specific repair mechanisms can speed up or slow down semantic coordination in dialog (see e.g., Healey, ; Healey, Mills, Eshghi, & Howes, ).…”
Section: The Cognitive Science Of Miscommunicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research data suggest that non--specific effects explain a considerable amount of the variation in patient outcomes in clinical trials. non-specific effects account for almost 60% of the variance in outcomes across clinical trials [1], indicating that non-specific treatment effects would be more important than specific effects [2] and that the effectiveness of medical procedures also depends on the quality of the physician−patient relationship [3]. essential elements of the physician−patient relationship include verbal and non-verbal communication, effective questioning and transmission of information, expression of empathy and concern, partnership and participatory decision-making [4,5].…”
Section: Introductionmentioning
confidence: 99%